The crisis of democratic theory : scientific naturalism & the problem of value - Purcell, Edward A. (University Press of Kentucky, 1973)
Widely acclaimed for its originality and penetration, this award-winning study of American thought in the twentieth century examines the ways in which the spread of pragmatism and scientific naturalism affected developments in philosophy, social science, and law, and traces the effects of these developments on traditional assumptions of democratic theory.
Keywords: Social sciences -- United States -- History.; Naturalism.; Democracy.; Naturalisme.; naturalism (philosophical movement); SOCIAL SCIENCE -- Essays.; SOCIAL SCIENCE -- Reference.; SOCIAL SCIENCE -- General.; Democracy; Naturalism; Social sciences; United States; Demokratie; Krise; Theorie; Democratie.; Politieke wetenschappen.; Electronic books.; History